Effects of transport inhibitors on the cellular uptake of liposomes from mycobacterium smegmatis by human monocytes dendritic cells - Nordin, Nor Asyikin (2024)
Nanotechnology such as liposomes is expected to play an important role in the rapidly growing field of nanomedicine. Liposomes are a type of lipid-based nanoparticles formed by the self-assembly of phospholipid molecules in an aqueous medium. Nowadays, it is widely used as an adjuvant or even a vehicle to deliver various therapeutic agents. Liposomes are biocompatible, biodegradable and have lower production costs, so due to these factors, much attention is devoted to them as potential carriers for targeted delivery in biomedical research for their adjuvant effects on dendritic cells (DCs). DCs are known as professional antigen-presenting cells (APCs), which can absorb, process and present antigens. DCs are at the centre of the immune system and capable of interacting with both B cells and T cells, thereby manipulating the humoral and cellular immune responses. It provides an essential link between innate and adaptive immunity. Due to strong immune activation function and natural adjuvant properties, it makes them a valuable target for antigen delivery. Based on literature, few studies investigating on the potential of liposomes derived from Mycobacterium smegmatis (M. smegmatis) (liposomes-Msmeg) as a lipid-based vaccine have been reported, however the uptake mechanism of liposomes-Msmeg by human monocytes DCs from human peripheral blood mononuclear cells (PBMC) and initiation of adaptive immune response have not been fully discovered. Thus, we aimed to investigate the cellular uptake mechanism of natural liposomes-Msmeg as a lipid-based vaccine by DCs. To assess cellular uptake mechanisms of liposomes-Msmeg, specific inhibitors such as chlorpromazine hydrochloride, filipin III and cytochalasin B which inhibit the specific pathway will be used. In this study, PBMC of healthy individuals was collected and sorted to study the monocyte populations by flow cytometry, while uptake mechanisms of liposomes-Msmeg will be viewed by field emission scanning electron microscope (FESEM) and confocal microscopy. Supernatant will be collected to measure the cytokine level by ELISA. Therefore, in this proposed study, we are going to fill up the gaps by investigating the uptake mechanisms of liposomes-Msmeg as a potent lipid-based vaccine by DCs from PBMC in healthy individuals.